Design and fabrication of stair climbing trolley / Aziz Iskandar Mohd Shafawi - Mohd Shafawi, Aziz Iskandar (2022)
Hand trolleys are devices that are used to transfer objects from one location to another. They are commonly used in a variety of industries, including warehouses, stores, marketplaces, and homes, with the primary aim of carrying physical items that are difficult to carry owing to their hefty weights. When it comes to moving products beyond ground level, however, there are restrictions where a hand trolley cannot be used, such as uneven terrain or any level above ground is not a simple job, especially if there are no lifting facilities (elevator, conveyer, etc). The main objectives of this project are to design CAD model of Stair Climbing Trolley using Solidwork software and to fabricate Stair Climbing Trolley using some modification from the conventional trolley. In general, the methods or steps of work to be conducted to complete this project will follow the product production flowchart. In conclusion, this project will be successful by design and fabricate the stair climbing trolley to provide the benefits to consumers like for sellers, warehouse workers or humans. Finally, the stair climbing trolley can operate satisfactorily if the objectives have been achieved.